Protecting image rights in the face of digitalization: A United States and European analysis - Heugas, Alix (John Wiley and Sons Inc, 2021)
The star of the movie “Rebel without a Cause,” James Dean,died in 1955. Yet the latest film he will officially be credited in,dates back to no sooner than 2020. Indeed,the movie “Finding Jack” will incorporate a hologram of James Dean,resurrected from the dead to play a character in this brand new performance under his name. This does not represent an exceptional singular case however. Technology is advancing at a drastic pace; which legislation sometimes struggles to keep up with. The novel ways of digitally reproducing human beings have brought along with them serious questions concerning Personality Rights protection. These rights diverge considerably from one jurisdiction to another,on a variety of topics such as the acknowledgement of posthumous protection or the scope of the right to privacy versus publicity rights,for example. This paper offers an evaluation of these rights,based on a comparative analysis across different civil and common law countries,which will hopefully provide an insight into how image rights are being safeguarded at present. The paper concludes proposing a potential future framework to ensure personality right protection in an increasingly digitized world. © 2021 The Authors. The Journal of World Intellectual Property published by John Wiley & Sons Ltd.
Keywords: ODS 16 - Paz, justicia e instituciones sólidas